Comparative analysis of video editors Adobe Premiere Pro and Sony Vegas Pro - Zyuzin, N. N. (ТДАТУ, 2020)
Adobe is known not only for its video editing software, but also for its photo and sound processing suites. For a person who is familiar with programs from this company, Adobe Premiere Pro will be easier to understand than Sony Vegas Pro from the familiar interface on out to the commands and hotkeys. Not every program has access to changing hotkeys, but since users are already familiar with them from other Adobe programs, they are not willing to customize them. For a person who is already editing in Adobe Premiere Pro, there is no reason to change anything, because it is more functional than its competitor.
Keywords: editing is; famous video; interface